Pelatihan dan Pendampingan Perhitungan RAB sebagai Kontrol dalam Pelaksanaan Pembangunan Insfrastruktur di Wilayah RT 11 RW 07 Desa Mranggen - Faizal Mahmud; Kukuh Wisnuaji Widiatmoko; Bambang Tutuko (Jurnal Pengabdian KOLABORATIF, 2024)
In building infrastructure, cost calculations are needed, organized in the form of a Budget Plan (RAB) according to government standards. The RAB provides an overview of the total cost required for building infrastructure or construction projects. Additionally, the RAB calculations can also determine the need for building materials, the number of workers required, and the duration of the project. This Community Service program aims to provide knowledge and new skills to the community on how to calculate the Budget Plan (RAB) for building both private homes and community infrastructure, such as meeting halls, neighborhood watch posts, water channels, and so on. The implementation method begins with interviews to assess understanding of creating an RAB, followed by socializing the benefits of making an RAB, training, and practical exercises on how to calculate the RAB. Subsequent steps include monitoring and evaluating the results of the calculations. This Community Service program equips the community with the skills to calculate the RAB for infrastructure development, better understand the volume of work calculations, determine material prices or unit prices for work, and prevent cost overruns during the construction phase.